Correlates of Numeracy Skills of Elementary Pupils in the Division of Northern Samar - Mondigo, Queenie E. (International Journal of Research in Interdisciplinary Studies, 2025)
This study examined multi-level factors influencing the numeracy skills of 936 Grade 5 pupils in Northern Samar, using a descriptive-correlational design with data from pupils and 10 math teachers across nine public schools. Findings revealed widespread gaps in foundational numeracy, with most pupils performing below proficiency. At the teacher level, there is a shortage of veteran educators, a disconnect between curriculum reforms and teacher training, and gaps in content knowledge due to a focus on general pedagogy over math-specific instruction. Although all teachers pursued graduate studies (30% with a Master’s degree, 70% enrolled), traditional materials remain favored, while tech tools and structured feedback are underused due to access and training limitations. Regression results showed no significant effect from teacher experience, degree title, materials, or feedback. Higher education had a negative impact (β = –.439), while training (β = .345) and learner-centered pedagogy (β = .313) were strong positive predictors of numeracy, stressing the value of relevant training and effective teaching strategies.